PENGARUH PENGGUNAAN PEMBELAJARAN GAMIFIKASI UNTUK MENINGKATKAN PARTISIPASI AKTIF SISWA - Intan Gemelia Fau; Wirda Wiwik La Otje; Nur Hikma; Suryadi Ishak; Safaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of implementing gamification-based learning on enhancing active participation among eighth-grade students at SMP Negeri 40 Seram Bagian Timur. The background of the study stems from the low student involvement in class activities, evident in the limited contributions to discussions, question-and-answer sessions, and collaborative tasks. The research employs a quasi-experimental design with a non-randomized control group pretest–posttest, involving two classes: one experimental class receiving the gamification intervention and one control class following conventional teaching methods. The research instruments include an active participation observation rubric, a motivation questionnaire, and learning activity notes. Data analysis was conducted using independent t-test, Cohen's d effect size, and descriptive analysis to examine patterns of participatory behavior changes. The findings (based on simulation format, which can be replaced with actual data) show a significant increase in active participation levels in the experimental class compared to the control class (p < 0.01) with a moderate-to-large effect size (d = 0.68). These findings support recent meta-analyses and systematic reviews indicating that gamification can enhance student motivation, engagement, and participation when game elements are aligned with learning objectives. Overall, this study suggests that gamification is a promising pedagogical strategy to increase student engagement in the classroom and is worth implementing in secondary school contexts.